(untitled) (Journal of Pharmaceutical Negative Results, 2023)
One of the main causes of morbidity in women of reproductive age is uterine. These widespread tumours are thought to be caused by a number of variables, but this just furthers our lack of understanding of their pathophysiology. The effects of fibroids on a woman's menstrual cycle or pelvic pressure symptoms are the most typical ways in which they present . The best diagnostic method for uterine fibroids appears to be ultrasound, with magnetic resonance imaging. The medical treatment toolbox has grown with the recent arrival of aromatase inhibitors and selective progesterone receptor modulators (SPRMs). A common therapy for fibroids that spares the uterus and preserves fertility is uterine artery embolization (UAE). The number of minimal access treatment alternatives has recently risen with the use of radiofrequency (VizAblateTM and AcessaTM) or ultrasound waves (MRgFUS) for uterine fibroid ablation.